Civil War in Ukraine: Scientific Approaches and the Factor of the Cossacks - Anton Bredikhin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. The events in Ukraine in 2013-2014 contributed to the manifestation of the Ukrainian political crisis, which led to the secession of the Crimean Peninsula, the Donetsk and Luhansk People’s Republics. The new Ukrainian authorities, realizing the impossibility of returning the Crimea, launched a military operation against the DPR and LPR, the so-called “ATO”. The general civil confrontation between Kiev on the one hand and Donetsk and Luhansk on the other hand led to the beginning of the civil war in Ukraine, the fact of which is not recognized by the Ukrainian authorities, but is presented as “Russian aggression”. Methods. Through institutional analysis, the study identifies approaches to understanding the factor of the civil war in Ukraine. Analysis. The participants of the armed confrontation, both on the part of Ukraine, and on the part of the DPR and LPR, are Ukrainian citizens. The fact that there are a significant number of Russian citizens among the militia, primarily from among the Cossacks, is due to the historical unity of the lands of the pre-revolutionary Region of the Don Army, socio-cultural and blood-related factors. The participation of the Cossacks in the conflict is of particular importance in the context of Ukraine’s positioning itself as a “Cossack country”. An important place in the understanding of the military confrontation is occupied by the transnationalization of political elites for the post-Soviet space, which acts as an impulse for the unity of the population of the former USSR. In a civil war, there is no boundary dividing the parties on civilizational, ethnic and linguistic grounds. But at the same time, some authors highlight the factor of regional identity. Results. Approaches to the definition of the civil war in Ukraine are revealed. The reluctance of the perception of the concept of “civil war” by the Ukrainian authorities is determined. The assessment of the further development of the civil war in the country is given.